Self-Leadership and Its Influence on the Engagement of Islamic Junior High School Teachers in the Covid-19 Period - Muslim, Moh; Hasan, Nur; Kholifah, Yusnia Binti (BRILIANT: Jurnal Riset dan Konseptual, 2022)
Teacher engagement is one of the main elements in encouraging the success of educational institutions. Teachers are the spearhead in the learning process and the implementation of various educational activities in schools. Therefore, it takes a high commitment of teachers in the implementation of education. The low commitment of teachers in activities and implementation of learning in schools will affect the success of the implementation of education. One of the factors that influence teacher engagement is the self-leadership of the teacher. Teachers who have good self-leadership can encourage the level of teacher engagement which will certainly have an impact on the success of education. The purpose of this study was to examine the effect of Self-Leadership on teacher engagement at MTs Maarif NU Blitar. The approach used is quantitative with the type of descriptive explanatory research. Data collection techniques through questionnaires or questionnaires. Data analysis used simple linear regression. The results of the data analysis show that the constant of 26,022 states that if there is no self-leadership value, the teacher engagement value is 26,022. The X regression coefficient of 0.380 states that for every additional 1 value of self-leadership, it will increase the value of teacher engagement by 0.380, which means that self-leadership has an influence on teacher engagement.